Clinical efficacy of sublingual immunotherapy tablets for allergic rhinitis is unlikely to be derived from in vitro allergen-release data. (2nd September 2019) - Canonica, Giorgio Walter; Devillier, Philippe; Casale, Thomas; Demoly, Pascal; Bos, Catherine; Karagiannis, Efstrathios; Passalacqua, Giovanni; Wahn, Ulrich; Mascarell, Laurent
ABSTRACT: Introduction : Allergen bioavailability underpins the efficacy and safety of SLIT tablets. Three product-related factors are likely to influence this: tablet potency, formulation and sublingual holding time. Areas covered : Tablet formulation determines the rate and extent of solubilized allergen release. Using validated in vitro dissolution assays, the two licensed grass pollen SLIT tablets are shown to release ≥85% of their total allergenic activity within several minutes. Sublingual holding time affects the contact duration between solubilized allergens and sublingual tissue. Maximal uptake of allergens by sublingual tissue requires ~5 minutes, with little uptake occurring within the first minute. A higher potency tablet with longer sublingual holding time would provide higher bioavailability, while faster rates of allergen release in vitro are unlikely to translate to a greater increase in bioavailability. Differences in dissolution times cannot serve as a surrogate of in vivo bioavailability, and are not related to differences in efficacy at the marketed tablet dosages. Rapid in vitro dissolution is likely not a key requirement for inducing a potent immune response. Expert opinion : In vitro dissolution cannot predict the clinical efficacy of SLIT tablets but could be important in immune tolerance and safety. In addition, a discontinuous administration regimen may have benefits for adherence and cost without compromising efficacy.